(untitled) (Medicine Today, 2021)
Introduction: Prevention of Mother to Child Transmission (PMTCT) program, offers a range of services for women of reproductive age living with or at risk of HIV to maintain health and stop their infants from acquiring HIV. PMTCT services should be commenced before conception and throughout pregnancy, labor and breast feeding. Around 1.4 million HIV infections among children were prevented between 2010 and 2018 by PMTCT program. UNFPO started antenatal screening program in collaboration with AIDS/STD program in Bangladesh from 2013, in 12 centers (BSMMU, 4 Medical College Hospitals, 3 Sadar Hospitals, 3 Health Complexes and Memon Maternity Hospital, Chittagong). Materials and Methods: Observational study of Antenatal and postnatal cases in HIV screening in KMCH during the period of Nov’2017 to March’2020. Results: From November 2017 to March 2020, total 18,911 patients screened, 11 patients were found HIV positive. 2 patients dropped out. Among 9 patients, 6 patients were detected in antenatal and 3 in postnatal period. 6 patients had vaginal delivery, 2 elective caesarean section and 1 patient had abortion. Screening was done by Alere Determine HIV- ½ Ag/Ab Combotest and diagnosis was confirmed by Uni-Gold HIV Rapid Test and First Response HIV 1-2-0 Card test. Conclusion: Following confirmation, ARV started with proper counseling. All babies were breast fed. The neonates were screened by PCR at their age of 45 days and found negative. WHO guideline was strictly maintained during labor conduction and cesarean sections. PMTCT program should be expanded in all institutions to detect cases, reduce transmission, contraception counselling to reduce confirmed cases. Medicine Today 2021 Vol.33(1): 7-11